1974
DOI: 10.1021/ac60347a022
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric determination of copper(I) and cobalt(II) with ferrozine

Abstract: Based on the selective reactivity of the compounds containing the ferroin grouping

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 4 publications
1
24
0
Order By: Relevance
“…In the present work, however, such tendency was not detected. Since ferrozine can form a water soluble complex with Cu + (Kundra et al, 1974), it is possible that lower amounts of Cu were also available for absorption by the plants in the Fe-starvation treatment, where ferrozine was added to the nutrient solution, than in the control treatment.…”
Section: Analysis Of Pixementioning
confidence: 99%
“…In the present work, however, such tendency was not detected. Since ferrozine can form a water soluble complex with Cu + (Kundra et al, 1974), it is possible that lower amounts of Cu were also available for absorption by the plants in the Fe-starvation treatment, where ferrozine was added to the nutrient solution, than in the control treatment.…”
Section: Analysis Of Pixementioning
confidence: 99%
“…It is known that high concentrations of other sample components (e.g. silicates or metals other than Fe) can interfere with the Fe analysis (Kundra et al 1974;Anastácio et al 2008;Im et al 2013) yet also Fe extraction can be affected as shown for intermediate reaction products of the denitrification process (Klueglein & Kappler 2013;Yan et al 2015). Apart from the commonly used separation of solid and liquid phase prior to Fe extraction (Weber et al 2006;Chakraborty et al 2011), the protocol suggested by Klueglein & Kappler (2013), using 40 mM sulfamic acid instead of 1 M HCl as extracting agent has been proven to be highly efficient and quantitatively accurate for the extraction of poorly crystalline Fe from bacterial batch cultures containing nitrite (Klueglein & Kappler 2013;Klueglein et al 2015;Li et al 2015;Xiu et al 2016) and was successfully applied to sediment and slurry samples (Laufer et al 2016a;Robertson et al 2016).…”
Section: Implications and Recommendation For Protocol Applicationmentioning
confidence: 99%
“…The sequential application of extraction protocols using increasing concentrations of acids allows the extraction of several Fe fractions from the very same sample, providing detailed information about the Fe mineral composition (Tessier et al 1979;Heron et al 1994;Poulton & Canfield 2005). The quantification of extracted Fe is commonly done using spectrophotometric assays (Braunschweig et al 2012;Verschoor & Molot 2013) based on agents such as ferrozine (Stookey 1970) or phenanthroline (Clark 1962 (Stookey 1970;Kundra et al 1974) or high concentrations of Fe III diss (Im et al 2013 It was therefore suggested by Klueglein & Kappler (2013) to replace HCl with sulfamic acid for Fe extraction in samples potentially containing nitrite. Fe extraction using sulfamic acid has proven to be successful in lab systems such as culture media as well as for environmental samples (Li et al 2015;Laufer et al 2016a;Robertson et al 2016;Xiu et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Because the reagent is specific for ferrous ions under the reaction conditions used (Attari and Jaselskis 1972), measurements of total iron content depend on prior reduction of any Fe 3 + present using 10°/o (w/v) hydroxylamine hydrochloride. Since copper, cobalt and nickel ions produce some interference at pH values close to neutral (Kundra et al 1974), the reaction mixture was re-equilibrated through addition of an ammonium acetate-ammonium hydroxide buffer (pH 8.7). Iron standards were prepared through serial dilutions of 1 mg/ml FeCl 3 ·6H 2 0 in the same 1 N HCI that samples were digested in.…”
Section: Ferrozine Reagent Was Obtained Through Hach Chemical Companymentioning
confidence: 99%